Refining the Indications for the Addition of Orbital Osteotomy during Anterior Cranial Base Approaches: Morphometric and Radiologic Study of the Anterior Cranial Base Osteology - DeBattista, Juan Carlos; Andaluz, Norberto; Zuccarello, Mario; Kerr, Robert G.; Keller, Jeffrey T. (Journal of Neurological Surgery Reports, 2014)
Objectives In anatomic and radiologic morphometric studies, we examine a predictive method, based on preoperative imaging of the anterior cranial base, to define when addition of orbital osteotomy is warranted.Design Anatomic and radiographic study.Setting In 100 dry skulls, measurements in the anterior cranial fossa included three lines and two angles based on computerized tomography (CT) scans taken in situ and validated using frameless stereotactic navigation. The medial angle (coronal plane) was the intersection between the highest point of both orbits and the midpoint between the two frontoethmoidal sutures to each orbital roof high point. The oblique angle (sagittal plane) was the intersection at the midpoint of the limbus sphenoidale.Results No identifiable morphometric patterns were found for our classification of anterior fossae; the two-tailed distribution pattern was similar for all skulls, disproving the hypothetical correlation between visual appearance and morphometry. Orbital heights (range: 6.6–18.7 mm) showed a linear relationship with medial and oblique angles, and they had a linear distribution relative to angular increments. Orbital heights > 11 mm were associated with angles ≥ 20 degrees and more likely to benefit from orbitotomy.Conclusion Preoperative CT measurement of orbital height appears feasible for predicting when orbitotomy is needed, and it warrants further testing.
Keywords: orbitotomy; skull base; frameless stereotaxy; anterior cranial base